2004
DOI: 10.1023/b:abme.0000007786.37957.65
|View full text |Cite
|
Sign up to set email alerts
|

Design Characteristics for the Tissue Engineering of Cartilaginous Tissues

Abstract: Tissues like the temporomandibular joint (TMJ) disc and the knee meniscus are often mistakenly viewed as a tantamount to hyaline cartilage, largely due to the absence of a comprehensive understanding of the distinguishing properties of cartilaginous tissues. Because of this confusion, fibrocartilaginous tissue engineering attempts may not be based on suitable experimental designs. Fibrocartilaginous tissues are markedly different than hyaline cartilage; however, the dearth of knowledge related to their cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
148
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(156 citation statements)
references
References 68 publications
5
148
1
2
Order By: Relevance
“…To understand basic cellular mechanisms underlying TMJ OA, we harvested primary MCCs. Because the mandibular condylar cartilage is distinct from knee hyaline articular cartilage, [3][4][5][6][7][8] we compared MCCs with HACs isolated from the knee joint. Our mRNA and protein profiling revealed that the two cell populations share overlaping gene/protein expression patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand basic cellular mechanisms underlying TMJ OA, we harvested primary MCCs. Because the mandibular condylar cartilage is distinct from knee hyaline articular cartilage, [3][4][5][6][7][8] we compared MCCs with HACs isolated from the knee joint. Our mRNA and protein profiling revealed that the two cell populations share overlaping gene/protein expression patterns.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mandibular condylar cartilage is distinct from other articular cartilages and possesses unique morphological, 3 functional, 4 biomechanical, [5][6][7] and biological 8 -11 properties. For example, the articular zone is the most superficial cellular layer that uniquely distinguishes the TMJ as a fibrocartilage.…”
Section: Fmodmentioning
confidence: 99%
“…The cells of the meniscus are referred to by some as fibrochondrocytes (Almarza et al, 2004), although there is evidence that there are at least 2 distinct populations present: chondrocyte-like cells are found when explants of the inner meniscus are cultured whilst elongated fibroblast cells are observed from explant cultures of the outer region. The morphology of the cells within the meniscus also varies with location in situ, being oval and fusiform in the superficial zone, to more rounded and polygonal in the deeper zone (reviewed in (Almarza et al, 2004) and (Dudhia et al, 2004) (ii) The Intervertebral Disc The intervertebral discs sit between the centrum of the spinal vertebrae, interfaced superiorly and inferiorly by hyaline cartilage endplates.…”
Section: (I) Meniscusmentioning
confidence: 99%
“…The morphology of the cells within the meniscus also varies with location in situ, being oval and fusiform in the superficial zone, to more rounded and polygonal in the deeper zone (reviewed in (Almarza et al, 2004) and (Dudhia et al, 2004) (ii) The Intervertebral Disc The intervertebral discs sit between the centrum of the spinal vertebrae, interfaced superiorly and inferiorly by hyaline cartilage endplates. At birth these constitute more than 50% of the intervertebral space but, during development, this reduces and the layer of hyaline cartilage becomes progressively thinner until in adulthood it is less than 1 mm thick.…”
Section: (I) Meniscusmentioning
confidence: 99%
“…A potential advantage of this approach is to generate neotissues with specific characteristics that are necessary for withstanding the mechanical complexity of joints. Given that the highly specialized biomechanical roles of musculoskeletal soft tissues are closely related to their matrix organization, 2 it has become of critical importance to capture the anisotropic functionality of native tissues during in vitro neotissue development.…”
mentioning
confidence: 99%